2017
DOI: 10.1159/000475888
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Specific Anti-Human Leukocyte Antigens Antibodies, Acute Rejection, Renal Function, and Histology in Kidney Transplant Recipients Receiving Tacrolimus and Everolimus

Abstract: Background: This analysis compared efficacy, renal function, and histology in kidney transplant recipients receiving tacrolimus (TAC) combined with everolimus (EVR) or mycophenolate (MPS). Methods: This was a retrospective analysis from a randomized trial in kidney transplant recipients who received a single 3 mg/kg dose of rabbit antithymocyte globulin (r-ATG), TAC, EVR, and prednisone (PRED; r-ATG/EVR, n = 85), basiliximab (BAS), TAC, EVR, and PRED (BAS/EVR, n = 102) or BAS, TAC, MPS, and PRED (BAS/MPS, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Different from studies demonstrating better renal function in patients on EVR versus MPS in combination with CsA, we observed no benefits on renal function. In agreement with our findings, previous studies using TAC instead of CsA also did not report renal function improvements in EVR regimens [29]. A possible explanation for this finding would be the potential lower nephrotoxic effect of therapeutic doses of TAC compared to CsA [30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Different from studies demonstrating better renal function in patients on EVR versus MPS in combination with CsA, we observed no benefits on renal function. In agreement with our findings, previous studies using TAC instead of CsA also did not report renal function improvements in EVR regimens [29]. A possible explanation for this finding would be the potential lower nephrotoxic effect of therapeutic doses of TAC compared to CsA [30].…”
Section: Discussionsupporting
confidence: 92%
“…). Similar noncompliance to predetermined TAC levels were observed in previous studies . In fact, one of the challenges of this association in current clinical practice is to determine the optimal mTORi and calcineurin inhibitor concentrations to maintain a good efficacy–toxicity balance.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have shown that renal function at 12 months was similar in patients receiving EVR or MPA in combination with TAC . The incomplete recovery of renal function observed from months 1 to 12 occurred despite comparable and low exposure to TAC.…”
Section: Discussionmentioning
confidence: 84%
“…The results are mixed to this in the literature. Some trials reported a higher incidence of dnDSA under mTOR-Is [ 16 , 42 45 ] and some did not [ 18 , 46 , 47 ]. The largest multicenter study to date comparing mTOR-Is with CNIs following renal transplantation (TRANSFORM) showed no negative effect for the mTOR-I in terms of dnDSA incidence and antibody-mediated rejection at 12 months [ 18 ].…”
Section: Discussionmentioning
confidence: 99%